Hemolysis and free hemoglobin revisited: exploring hemoglobin and hemin scavengers as a novel class of therapeutic proteins - Schaer, Dominik J. (American Society of Hematology, 2013)
Hemolysis occurs in many hematologic and nonhematologic diseases. Extracellular hemoglobin (Hb) has been found to trigger specific pathophysiologies that are associated with adverse clinical outcomes in patients with hemolysis, such as acute and chronic vascular disease, inflammation, thrombosis, and renal impairment. Among the molecular characteristics of extracellular Hb, translocation of the molecule into the extravascular space, oxidative and nitric oxide reactions, hemin release, and molecular signaling effects of hemin appear to be the most critical. Limited clinical experience with a plasma-derived haptoglobin (Hp) product in Japan and more recent preclinical animal studies suggest that the natural Hb and the hemin-scavenger proteins Hp and hemopexin have a strong potential to neutralize the adverse physiologic effects of Hb and hemin. This includes conditions that are as diverse as RBC transfusion, sickle cell disease, sepsis, and extracorporeal circulation. This perspective reviews the principal mechanisms of Hb and hemin toxicity in different disease states, updates how the natural scavengers efficiently control these toxic moieties, and explores critical issues in the development of human plasma–derived Hp and hemopexin as therapeutics for patients with excessive intravascular hemolysis.